Sosialisasi dan Edukasi Sertifikasi Label Halal UMKM Masyarakat Desa Sapit - Mispandi (Arfah BHMS Foundation, 2025)
This Community Service Activity aims to Socialize and educate Halal Label Certification for MSMEs is to educate and help the people of Sapit Village to know the importance of Halal Labels on MSME products and help the Community to obtain Halal Certification for their MSME products. The methods of this activity are Conducting field observations, Conducting MSME data collection, Activity Planning, Implementing socialization. The results of the activity showed that 80% of participants were very satisfied and 20% were quite satisfied with the implementation of the socialization activity. Keywords (bold): Socialization, Certification, halal label.